Media Development of the Wix Web for Teaching Report Text Materials - Rahmi Amalia; John Pahamzah (Journal of English Language Teaching and Cultural Studies, 2023)
The aims of this research were (1) to find out the students’ needs in learning report text at the tenth grade students, (2) to find out how to develop Wix Web as a media for teaching report text, and (3) to find out the appropriateness of Wix Web for teaching report text at the tenth grade students. This research adapted the Research and Development (R&D) proposed by Borg and Gall (2003) through 10 procedures. The participants of the research involved an English teacher and 40 tenth grade students at SMAN 3 Kota Serang. This research also used the students’ open-ended questionnaires, semi-structured interview, students’ assessment sheets, material, and media experts’ validation forms as the instruments. The data of research which were analyzed qualitatively and quantitatively showed that the English teacher and the students needed a Wix Web. The developed media obtained the percentage scores of 84% and 86% in the preliminary field testing, 92% and 96% in the main field testing, and 100% in the operational field testing from the material and media experts. Meanwhile, the developed media obtained the percentage scores of 85,10%, in the preliminary field testing, 88,35%, in the main field testing, and 96,55%  in the operational field testing from the students. Those results showed that the developed media of Wix Web was categorized into “Valid” criteria and it was appropriate to be used and applied for teaching and learning the secondary high students of SMA Negeri 3 Kota Serang.